2019
DOI: 10.1101/550624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LatentToxoplasma gondiiinfection increases soluble mutant huntingtin and promotes neurodegeneration in the YAC128 mouse model of Huntington’s disease

Abstract: Toxoplasma gondii causes a prevalent neuroinvasive protozoal pathogen that in immune competent individuals results in latent infection characterized by intra--cellular parasite cysts in brain. Despite life--long infection, the role of latent toxoplasmosis on chronic neurodegenerative processes is poorly understood. Huntington's disease (HD) is a progressive neurodegenerative disorder caused by a dominant CAG repeat expansion in the huntingtin gene (HTT) that results in the expression and accumulation of mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…Interestingly, a recent study reported on unmasking of two cases of HD by the COVID-19 infection [50]. Moreover, two different HD mouse models infected with Toxoplasma gondii, displayed aberrant activation of the inflammatory kynurenine pathway, reduced number of CD8 + T cells, elevated levels of soluble mHTT in brain, increased striatal neurodegeneration, and accelerated death [51,52]. Colonization of transgenic Drosophila models of HD with E. coli accelerates the aggregation of an amyloidogenic mutant HTT 586 (N-terminal 586 amino acids with 120Qs) fragment, induces motor impairment and shortens lifespan.…”
Section: Pathobionts and Pathogens As Triggers Of Neurological Sympto...mentioning
confidence: 99%
“…Interestingly, a recent study reported on unmasking of two cases of HD by the COVID-19 infection [50]. Moreover, two different HD mouse models infected with Toxoplasma gondii, displayed aberrant activation of the inflammatory kynurenine pathway, reduced number of CD8 + T cells, elevated levels of soluble mHTT in brain, increased striatal neurodegeneration, and accelerated death [51,52]. Colonization of transgenic Drosophila models of HD with E. coli accelerates the aggregation of an amyloidogenic mutant HTT 586 (N-terminal 586 amino acids with 120Qs) fragment, induces motor impairment and shortens lifespan.…”
Section: Pathobionts and Pathogens As Triggers Of Neurological Sympto...mentioning
confidence: 99%
“…Dysregulation of dopamine and serotonin may enhance the risk of schizophrenia, BD, epilepsy, depression, anxiety, aggression, impulsivity, suicide, OCD and Parkinson's disease. It may also modify personality traits, such as extraversion, neuroticism and conscientiousness [29,30,36,37,42,88,110,[112][113][114]. The infection can also be associated with impaired cognitive functions, such as learning, memory, attention and psychomotor performance, which result from the parasite-induced increase in glutamate levels and enhanced activation of gamma-aminobutyric acid (GABA) receptor signalling [115].…”
Section: Alteration Of Neurotransmitter Levelsmentioning
confidence: 99%